Kompetensi Pegawai Balai Teknik Perkeretaapian Wilayah Sumatera Bagian Selatan - Illahi, Firman Tri (Direktorat Riset dan Pengabdian Kepada Masyarakat Universitas Bina Darma, 2019)
Government have to implement a structured and organized governance system well. In the implementation of tasks and functions, government supported by human resources as executor. The qualified of civil servants certainly expected to provide optimal performance results. This research using a quantitative research techniques by data collection methods of observation and analysis of case while the methode of solving the case using interviews based on the results of the analysis and discussion. Human resource who qualified expected to reach optimal result in any job performance. They must be have sufficient knowledge, skill and also competence to do job and task. By considering the importance of the investment value of human resources, it is important to improve the quality of human resources in terms of knowledge, attitudes and skills in order to obtain the optimality of performance for government agencies, through the recruitment in accordance with the specification requirements, education and training which tailored to the tasks and services performed as well as the clarity of procedures and regulations decided to become a good governance.